2007
DOI: 10.1086/518965
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nasal Colonization Among Patients With Community-Associated Methicillin-ResistantStaphylococcus aureusInfection and Their Household Contacts

Abstract: The frequency of CA-MRSA colonization among household members of patients with CA-MRSA infections is higher than rates reported among the general population. Among colonized household members, only half of the MRSA strains were related to the patients' infective isolate. Within the same household, multiple strains of CA-MRSA may be present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 17 publications
3
49
0
Order By: Relevance
“…A recent study reported 19% MRSA transmission to household contacts from index persons treated in home health care settings (23). Most studies reporting on MRSA transmission from index persons to household members differ in study methods, and therefore, comparison of study outcomes with that of our study cannot yield robust conclusions (14,15,22,23,36). These studies differ mostly in the sites cultured.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A recent study reported 19% MRSA transmission to household contacts from index persons treated in home health care settings (23). Most studies reporting on MRSA transmission from index persons to household members differ in study methods, and therefore, comparison of study outcomes with that of our study cannot yield robust conclusions (14,15,22,23,36). These studies differ mostly in the sites cultured.…”
Section: Discussionmentioning
confidence: 72%
“…The spread of MRSA among household contacts has been reported previously, but the observed MRSA transmission rates to household contacts are variable (5,14,16,18,22,23,36). Johansson et al (18) observed that in 22 of 51 index persons (43%), MRSA was transmitted to one or more household contacts.…”
Section: Discussionmentioning
confidence: 89%
“…2,22 Proper hand hygiene (Box 1), 8 as well as cleaning of equipment and the environment, is important in both the home and institutions where health care is provided. In the home, it is neither realistic nor practical to attempt to isolate a family member who is colonized or infected with MRSA.…”
Section: Prevention and Controlmentioning
confidence: 99%
“…Antimicrobial resistance may also evolve or be acquired in the community and be introduced into a health care facility from the community, where the infection can spread widely. [1][2][3][4][5][6] The suggestions presented in this review provide a basic approach that can be applied to prevent the transmission of current antimicrobial-resistant pathogens and those that may arise in the future.…”
mentioning
confidence: 99%
See 1 more Smart Citation